Education and Social Change on How Education Used to Be and How It Is Today - Latifah, Mar'atul; Faelasup (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Education today is very important for technological and human progress, even education is the main key to finding work, because the more advanced the development of technology, what makes people have to be more diligent to improve education, education will be used forever. Even now, the government has facilitated a lot of young people to be more interested in pursuing education, unlike in the past, only the children of the rich can afford education. Therefore, as a young generation, we must be more enthusiastic about education. The formulation of the problem is (1) How was education in the past with today's (2) What is the difference between the situation in the past and today. This study uses a qualitative method by approaching the community of teachers and parents which aims to obtain information about how opinions and ways of responding to the differences in education in the past and education are today. By looking for information about the differences in education, we will find out how to learn well so that children are able to follow education according to the times. This study aims to find out how the development of education in the past and today is and to find out what the differences are in the situation in the past and today. The findings of the research that have been carried out are that there are very many differences between the past and present, both in the situation and in the teaching and learning process. The supporting factors are (a) with changes every year that make it easier for teachers and students to be able to access material from various sources (b) there is support from teachers and parents who make children more enthusiastic about learning. The inhibiting factors are (a) a change in the curriculum (b) a lack of parental knowledge in keeping up with the times.